SOCIAL EDUCATION AT HIGHER MEDICAL SCHOOL - Denis E. Firsov (Высшее образование в России)
The development of social education in modern Russia became an important part of an overall process of social and innovative modernization of Russian society. Implementing of the educational standardin thefield of social workin Yaroslavl State Medical Academy confirms propriety of the development of socially oriented educational programs at higher medical school.